2010
DOI: 10.1158/1078-0432.ccr-09-2828
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive Biomarkers of Sensitivity to the Phosphatidylinositol 3′ Kinase Inhibitor GDC-0941 in Breast Cancer Preclinical Models

Abstract: Purpose: The class I phosphatidylinositol 3′ kinase (PI3K) plays a major role in proliferation and survival in a wide variety of human cancers. A key factor in successful development of drugs targeting this pathway is likely to be the identification of responsive patient populations with predictive diagnostic biomarkers. This study sought to identify candidate biomarkers of response to the selective PI3K inhibitor GDC-0941.Experimental Design: We used a large panel of breast cancer cell lines and in vivo xenog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
171
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(189 citation statements)
references
References 47 publications
17
171
1
Order By: Relevance
“…Together with previous studies targeting the PI3K pathway alone or in combination with MEK inhibition, these results indicate that levels of phosphorylated S6 may be an effective biomarker of response to targeting these key survival pathways (32)(33)(34).…”
Section: Assessment Of Cell Death Markers Following Dual Targeting Ofsupporting
confidence: 76%
“…Together with previous studies targeting the PI3K pathway alone or in combination with MEK inhibition, these results indicate that levels of phosphorylated S6 may be an effective biomarker of response to targeting these key survival pathways (32)(33)(34).…”
Section: Assessment Of Cell Death Markers Following Dual Targeting Ofsupporting
confidence: 76%
“…This indicates that a majority of these lines at least partly depend on PI3K signaling for their proliferation. We observed that PIK3CA mutation, but not PTEN loss, correlated with sensitivity to PI3K inhibition, as demonstrated before for breast cancer regardless of hormone receptor or HER2 status (15).…”
Section: Knockdown Of Igf1r Sensitizes Hcc1806 To Pi3k Inhibition By supporting
confidence: 86%
“…Cell lines harboring PIK3CA mutations have been shown to be more sensitive to a selective class I PI3K inhibitor 11 and luminal breast cancer cells preferentially respond to PI3K inhibitors. 6 As PIK3CA mutations have been found in 18-40% of human breast cancer, it was hypothesized that these mutation could be responsible for the deregulation in the signaling pathway and consequently these patients would be most suitable for PI3K/ mTOR pathway inhibition.…”
Section: Discussionmentioning
confidence: 99%